Stressful Daylight: Differences in Diel Rhythmicity Between Albino and Pigmented Fish - Valchářová, Tereza; Slavík, Ondřej; Horký, Pavel; Stará, Alžběta; Hrušková, Iveta; Maciak, Matúš; Pešta, Michal; Velíšek, Josef (Frontiers in Ecology and Evolution, 2022)
In laboratory experiments, variously colored strains of animals, including those with albino phenotypes, are commonly used. The melanocortin theory suggests, however, that coloration phenotypes alter animal physiology and behavior. Animals with the albino phenotype show photoreceptor degradation associated with lowered visual accuracy, escape reactions, etc., presumably accompanied by prevailing nocturnal activity and lowered aggressiveness. This assumption was tested in small groups of albino and pigmented European catfish, Silurus glanis, during the diel cycle. The frequency of agonistic interactions was observed during mutual contests for shelters, and subsequently, blood plasma, brain, gill, and liver samples were collected to evaluate stress parameters. In an experimental arena with shelters, the light/dark rhythmicity of locomotor activity and aggressiveness of the two phenotypes were comparable; the peak was observed at night, and a lower peak was observed at dawn. In an experimental stream without shelters, the peak of locomotor activity occurred at night for only the pigmented phenotype. In the evaluation of four antioxidants and one oxidative stress indicator, representing a total of 15 indices, albino fish showed significant rhythmicity for eight indices, whereas pigmented catfish showed significant rhythmicity for five indices. The production of blood stress parameters with the peak during the day occurred only in albino fish. A complex model was fitted with the aim of evaluating the links between behavioral and biochemical indices. Time periodicity was modeled using a sine wave and confirmed parallel courses of agonistic interactions in the catfish groups; the peak at dawn was associated with a 4.08-fold (conf. int. 3.53–4.7) increase in such interactions. The changes in glucose and superoxide dismutase concentrations varied with phenotype, while the effects of cortisol, lactate and catalase did not. In summary, the rhythmicity of locomotor activity and changes in the aggressiveness of catfish were influenced by shelter availability, and the effect of light-induced stress was more apparent in albino fish than in pigmented conspecific fish. The results suggested that laboratory-raised animals with pigmentation patterns naturally occurring in the wild show more reasonable values during experiments than those with an albino phenotype.